2022
DOI: 10.1093/gji/ggac093
|View full text |Cite
|
Sign up to set email alerts
|

Stress changes caused by exsolution of magmatic fluids within an axisymmetric inclusion

Abstract: Summary In volcanic regions ascending magma is subject to depressurization and is generally accompanied by exsolution of volatiles. We blackassume a process in which these volatiles propagate upward across newly fractured and permeable rock layers, bringing a sharp increase of pore pressure and temperature within a thin disk-shaped region (inclusion). Thermo-poro-elastic (TPE) inclusion models provide a mechanism to explain seismicity and deformation induced by p and T changes in absence of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…1−] ΔV (Belardinelli et al, 2019;Belardinelli et al, 2022). Closed analytical solutions to Eqs 1-3 can be derived only under simplified assumptions for material properties, pore-pressure and temperature change distributions, and domain and source geometries.…”
Section: Thermo-poro-elastic Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…1−] ΔV (Belardinelli et al, 2019;Belardinelli et al, 2022). Closed analytical solutions to Eqs 1-3 can be derived only under simplified assumptions for material properties, pore-pressure and temperature change distributions, and domain and source geometries.…”
Section: Thermo-poro-elastic Deformationmentioning
confidence: 99%
“…Examinations of both gravity (Na et al, 2015) and, more recently, thermo-poro-elastic deformation (Mantiloni et al, 2020) have shown that the solutions are accurate under the assumption that the height h of the cylinder is much smaller than its radius R (h/R ≪ 1). The analytical solutions for thin diskshaped sources (Mantiloni et al, 2020) can be easily generalized to model thick cylindrical sources by stacking two or more disks (Nespoli et al, 2021;Belardinelli et al, 2022).…”
Section: Cylindrical Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The stress evolution with considering 4D analysis of strain-dependent elasticity and application in subsalt carbonates was investigated in comparison with FEM results. The special geometry of a thin diskshaped resource subject to depressurization was explored via the thermoporoelastic inclusion model [15]. In addition, the related topics on the stress response to pore pressure fluctuations around resources [16,17] and the nonprobabilistic model to solve the effect of crack size uncertainty [18] were analytically evaluated.…”
Section: Introductionmentioning
confidence: 99%